EFFECTIVE STRATEGIES FOR TEACHING ENGLISH GRAMMAR IN SECONDARY SCHOOL CLASSROOMS - Umarova Iroda Ravshanovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract:This article explores practical and engaging strategies for teaching English grammar in secondary school settings. Grammar is a key part of learning English, but many students find it difficult or uninteresting. The article explains how teachers can make grammar lessons more meaningful through the use of real-life examples, interactive activities, storytelling, and visual materials. It also emphasizes the importance of clear explanations, student-centered methods, and regular practice. By creating a positive and supportive classroom environment, teachers can help learners build strong grammar skills and improve their communication in English.